2002
DOI: 10.1097/01.asn.0000019781.90630.0f
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Regulation of Renal Oxygen Consumption in Spontaneously Hypertensive Rats

Abstract: Abstract. Abnormalities of nitric oxide (NO) and oxygen radical synthesis and of oxygen consumption have been described in the spontaneously hypertensive rat (SHR) and may contribute to the pathogenesis of hypertension. NO plays a role in the regulation of renal oxygen consumption in normal kidney, so the response of renal cortical oxygen consumption to stimulators of NO production before and after the addition of the superoxide scavenging agent tempol (4-hydroxy-2,2,6,6-tetramethyl piperidine-1-oxyl) was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 45 publications
(53 reference statements)
3
42
0
Order By: Relevance
“…It has been shown that both ANG II receptor blockers (ARBs) and the combination of hydrochlorothiazide, hydralazine, and reserpine (triple therapy) can normalize blood pressure in the SHR rat; however, only ARBs reduce excretion of ROS reaction product 8-iso-PGF 2␣ . Interestingly, PO 2 values are lower in the SHR, and this too is normalized by ARB therapy or treatment with the SOD mimetic tempol (1,164). Tempol also has been shown to enhance medullary perfusion (183).…”
Section: Role Of Dvr Endothelia In the Regulation Of Vasoactivitymentioning
confidence: 99%
“…It has been shown that both ANG II receptor blockers (ARBs) and the combination of hydrochlorothiazide, hydralazine, and reserpine (triple therapy) can normalize blood pressure in the SHR rat; however, only ARBs reduce excretion of ROS reaction product 8-iso-PGF 2␣ . Interestingly, PO 2 values are lower in the SHR, and this too is normalized by ARB therapy or treatment with the SOD mimetic tempol (1,164). Tempol also has been shown to enhance medullary perfusion (183).…”
Section: Role Of Dvr Endothelia In the Regulation Of Vasoactivitymentioning
confidence: 99%
“…Adler et al (44) showed that, because NO is a suppressor of mitochondrial respiration, depletion of NO by oxidative stress may stimulate mitochondrial respiration and uncouple it from chemical energy consumption, resulting in tissue hypoxia ( Figure 2E). Kidneys of the spontaneously hypertensive rat (SHR), which characteristically undergo oxidative stress, revealed enhanced oxygen usage relative to tubular sodium transport and lower intrarenal pO 2 (45).…”
Section: Oxidative Stress and Inefficient Cellular Respirationmentioning
confidence: 99%
“…Specifically, the oxygen tension of the kidney cortex and medulla has been shown to be approximately 10 mm Hg lower than normal in spontaneously hypertensive rats and other models of hypertension as well as in hypertensive patients. 15,89,[144][145][146] The role of hypertension in the progression of CKD was first described in 1914 by Volhard and Fahr. 13 Subsequently, it was appreciated that hypertension predisposes to kidney failure by inducing renal hypoxia.…”
Section: Hypertensionmentioning
confidence: 99%